ANALISIS KESIAPAN MAHASISWA KOTA MEDAN SEBAGAI BAGIAN DARI BONUS DEMOGRAFI DALAM ERA MASYARAKAT EKONOMI ASEAN (MEA) - Farihah Farihah; Dwi Wahyuni Nurwihastuti; Apiek Gandamana (JURNAL KELUARGA SEHAT SEJAHTERA, 2018)
ABSTRACTStudents as part of the 2/3 of the Indonesian population on demographic bonuses have to prepare themselves not to become foreign in their own country in this era of MEA. The way to improve the quality of education and student skills so that later after college can compete in getting a job with other college graduates in ASEAN countries. Medan City is a student city in North Sumatra Province, this indication is marked by many higher education institutions. The number of private and public universities in Medan is 60 universities. Students from these universities come from various regions in North Sumatra Province with various qualities. The objectives of this research are: (1) To know the readiness of the students as part of the demographic bonus if viewed from the aspect of knowledge and understanding towards MEA (ASEAN Economic Community), (2) To know the readiness of the students as part of the demographic bonus when viewed in terms of skill to MEA (ASEAN Economic Community), and (3) Knowing the readiness of the students as part of the demographic bonus when viewed from the experience point of the MEA (ASEAN Economic Community). The results showed that the readiness of students as part of the demographic bonus when viewed in terms of knowledge and understanding of the MEA provides a fairly promising picture. Most students show considerable knowledge and understanding of the MEA itself. Student readiness as part of the demographic bonus in terms of skills still needs to be improved. Students in the city of Medan do not have adequate skills evenly so can be worried about having difficulties in facing the MEA. While the readiness of students as part of the demographic bonus when viewed in terms of experience has not described the maximum results. Students are generally still minimal experience. Therefore, there is still a need to improve further experience in creating students who are full of experience. Whether you realize it or not, it's an experienced student who can compete in the MEA era. Keywords: students, Medan City, demographic bonus, MEA